Torah as teacher : the exemplary Torah student in Psalm 119 - Reynolds, Kent Aaron. (Vetus Testamentum, Supplements, 2010)
Despite extensive study of the poetic features of Psalm 119, the conceptions it advocates and its contribution to developing Judaism have not been well understood; indeed some scholars have dismissed the psalm as containing little more than wearisome repetition. Reynolds distinguishes between the psalmist and the speaker within the psalm. The psalmist portrays the speaker as an exemplary Torah student and thereby promotes the contemplation of Torah as a facet of ethical instruction. Using this new perspective, Reynolds contributes a fresh and coherent understanding of the ideas in Psalm 119. He explains the function of its length and highlights its emphasis on Torah study that became axiomatic in Rabbinic Judaism.